Novel biorenewable composite of wood polysaccharide and polylactic acid for three dimensional printing. (1st May 2018) - Xu, Wenyang; Pranovich, Andrey; Uppstu, Peter; Wang, Xiaoju; Kronlund, Dennis; Hemming, Jarl; Öblom, Heidi; Moritz, Niko; Preis, Maren; Sandler, Niklas; Willför, Stefan; Xu, Chunlin
Highlights: A solvent blending approach for evenly mixing two polymers was proposed. Hotmelt extrusion of composites of wood polysaccharides and polylactic acid was demonstrated. 3D scaffold prototypes of wood hemicellulose composites were successfully printed. Mechanical and morphological properties of composite filament and scaffolds were measured and the results compared. Abstract: Hemicelluloses, the second most abundant polysaccharide right after cellulose, are in practice still treated as a side-stream in biomass processing industries. In the present study, we report an approach to use a wood-derived and side-stream biopolymer, spruce wood hemicellulose (galactoglucomannan, GGM) to partially replace the synthetic PLA as feedstock material in 3D printing. A solvent blending approach was developed to ensure the even distribution of the formed binary biocomposites. The blends of hemicellulose and PLA with varied ratio up to 25% of hemicellulose were extruded into filaments by hot melt extrusion. 3D scaffold prototypes were successfully printed from the composite filaments by fused deposition modeling 3D printing. Combining with 3D printing technique, the biocompatible and biodegradable feature of spruce wood hemicellulose into the composite scaffolds would potentially boost this new composite material in various biomedical applications such as tissue engineering and drug-eluting scaffolds.